Comparative Efficacy of Alcohol-Based Chloroxylenol, Triclosan, and Gentamicin in Inhibiting Staphylococcus aureus Biofilm Formation - Muhammad Jundi Aziz Ashari; Agung Dwi Wahyu Widodo; Brian Eka Rachman (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2026)
Highlights: The combination of alcohol with triclosan and alcohol with chloroxylenol was effective in inhibiting the growth of S. aureus biofilms. Lower concentrations of gentamicin resulted in optical density (OD) values above the cut-off, suggesting that these doses were insufficient for biofilm inhibition and might potentially contribute to the persistence or stimulation of S. aureus biofilm growth.   Abstract Introduction: This study investigated the comparative efficacy of alcohol-based chloroxylenol, alcohol-based triclosan, and gentamicin in inhibiting Staphylococcus aureus biofilm formation. Biofilms formed by S. aureus present significant clinical challenges due to their antibiotic resistance and persistence in nosocomial infections. Methods: This study used the crystal violet assay with an enzyme-linked immunosorbent assay (ELISA) reader to evaluate S. aureus cultures treated with various antimicrobials. The treatments included chloroxylenol (10, 100, 1,000 ppm), triclosan (0.3, 3, 30 µg/ml), and gentamicin (5, 10, 15 mg/ml). The experiment consisted of three groups based on treatment type (n=72), each with three dosage levels (n=8). It was analyzed using the International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) version 27.0. A probability p<0.05 was considered significant. Results: The first group, chloroxylenol with alcohol, demonstrated significant inhibitory effects (n=24, p=0.007). The second group, triclosan with alcohol, exhibited the strongest antibiofilm activity (n=24, p=0.001). In contrast, the third group, gentamicin, showed no significant inhibitory effect (n=24, p=0.21). Conclusion: Chloroxylenol and triclosan exhibited significant inhibition (p=0.007 and p=0.001), whereas gentamicin did not (p=0.21). It also suggested that suboptimal gentamicin doses may contribute to biofilm persistence and adaptive responses in S. aureus. These findings underscore the potential of alcohol-based chloroxylenol and triclosan as effective agents for biofilm inhibition and highlight the need for reconsidering the role of gentamicin in treating biofilm-associated infections. Further research is warranted to explore optimal dosing strategies and the mechanisms underlying biofilm resistance.